An Agro-Food Waste Commercial Utilisation Behaviour Lens among Urban Agro-producer Households in a Developing Economy - Karani, Charles; Gido, Eric; Bett, Hillary (Applied Studies in Agribusiness and Commerce, 2021)
Small-urban farm businesses utilise agro-food waste emanating from own production and other levels of food supply chain activities to supplement conventional inputs. Out of these, the food produce surplus from agro-producer households is offloaded to the urban market. As such, the aim of the study was to assess the determinants of agro-food waste commercial utilisation behaviour among urban agro-producer households. An electronically-designed research tool was administered to 456 agro-producer households to collect self-reported estimates of their agro-food waste utilisation behaviour. Results indicated higher budget share towards conventional inputs (0.73) compared to agro-food waste (0.27) but the observed suboptimal production intensification could be rectified with increased use of agro-food waste. Structural equation modelling results indicated that attitude, environmental awareness and concern, motivation and perceived moral obligation had positive significant influence on commercial utilisation intention. The adopted constructs for the model could explain 79.1% of the commercial utilisation behaviour variance. Furthermore, commercial utilisation intention, risk perceptions and perceived behavioural control had significant influence on the commercial utilisation behaviour. Findings are an indicator that agro-food waste commercial utilisation intentions among small-urban farm businesses would likely transition to commercial utilisation behaviour. Since behaviour can be learnt and developed, aspects that contribute to commercial utilisation intentions and behaviour would need to be stimulated. As a strategy of reducing the collectible waste, urban authorities may introduce tailor-made programs meant to stimulate commercial utilisation intention and behaviour in small-urban farm businesses. In valuation of agro-food waste, methodologies that could factor in utility would provide more precise insights in its commercial utilisation.